Tingkat Pengetahuan Remaja terhadap Swamedikasi Obat Analgesik pada Dismenorea di Desa Jenggala, Lombok Utara, NTB - Hasanah, Uswatun; Kiromah, Naelaz Zukhruf Wakhidatul; Herniyatun, H (Prosiding University Research Colloquium, 2022)
Adolescence is a period of transition from children to adulthood, it is characterized by physical, psychological and psychosocial changes. The process of adolescents experiencing puberty, one of the characteristics is knowing menstruation, it is not uncommon for adolescents to experience reproductive problems, one of which is dysmenorrhea or menstrual pain. Management of dysmenorrhea can be done with pharmacological and non-pharmacological treatment, this is based on the knowledge of the individual about self-medication of analgesic drugs. This activities was conducted to determine the knowledge of adolescents on analgesic drugs in self-medication of menstrual pain. Data analysis used the Shapiro-Wilk test with a significance level of 0.05 (p = 0.05), the results of data that were not normally distributed were then carried out with the Wilcoxon test, the significant value obtained was 0.000 (p <0.05) which indicates a relationship or influence on the level of knowledge of adolescents in Jenggala village before and before counseling.